2018
DOI: 10.3389/fmicb.2018.00599
|View full text |Cite
|
Sign up to set email alerts
|

The Small Regulatory RNAs LhrC1–5 Contribute to the Response of Listeria monocytogenes to Heme Toxicity

Abstract: The LhrC family of small regulatory RNAs (sRNAs) is known to be induced when the foodborne pathogen Listeria monocytogenes is exposed to infection-relevant conditions, such as human blood. Here we demonstrate that excess heme, the core component of hemoglobin in blood, leads to a strong induction of the LhrC family members LhrC1–5. The heme-dependent activation of lhrC1–5 relies on the response regulator LisR, which is known to play a role in virulence and stress tolerance. Importantly, our studies revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 60 publications
2
30
0
1
Order By: Relevance
“…(Mollerup et al, 2016). In contrast to the other six LhrC sibling sRNAs, the expression of Rli33-1 is not induced by heme toxicity (Dos Santos et al, 2018). Alongside LhrC1-5, the expression of Rli33-1 is required for L. monocytogenes infection of macrophages (Mraheil et al, 2011).…”
Section: Trans-acting Srnas Directly Dependent On σ Bmentioning
confidence: 99%
“…(Mollerup et al, 2016). In contrast to the other six LhrC sibling sRNAs, the expression of Rli33-1 is not induced by heme toxicity (Dos Santos et al, 2018). Alongside LhrC1-5, the expression of Rli33-1 is required for L. monocytogenes infection of macrophages (Mraheil et al, 2011).…”
Section: Trans-acting Srnas Directly Dependent On σ Bmentioning
confidence: 99%
“…As whole human blood contains components integral to the host's immune response, and surface-exposed proteins are readily recognized by the immune system, the LhrCmediated down-regulation of OppA, LapB, and TcsA might represent a mechanism by which L. monocytogenes evades host immunity [12]. More recently, we have shown that LhrC1-5 are induced in response to excess heme, the core component of hemoglobin in blood [25]. We demonstrated that LhrC1-5 contribute to the adaptation of L. monocytogenes to excess heme, and that LhrC1-5 down-regulate the expression of genes involved in heme uptake and utilization, including lmo2186, lmo2185 (which encode the heme-binding proteins Hbp1 and Hbp2, respectively) and lmo0484 (which encodes a heme oxygenase-like protein) [25].…”
Section: Discussionmentioning
confidence: 95%
“…More recently, we have shown that LhrC1-5 are induced in response to excess heme, the core component of hemoglobin in blood [25]. We demonstrated that LhrC1-5 contribute to the adaptation of L. monocytogenes to excess heme, and that LhrC1-5 down-regulate the expression of genes involved in heme uptake and utilization, including lmo2186, lmo2185 (which encode the heme-binding proteins Hbp1 and Hbp2, respectively) and lmo0484 (which encodes a heme oxygenase-like protein) [25]. As previously demonstrated for oppA and lapB, we found that LhrC4 interacts with lmo2186, lmo2185, and lmo0484 mRNAs and, for lmo0484, LhrC4 uses a CU-rich loop for base-pairing to the AG-rich RBS of the mRNA [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rli33-1 sRNA belongs to the multicopy family LhrC, encompassing 7 members [ 77 ]. Besides Rli33-1, LhrC sRNAs, comprising LhrC1-5 and Rli22, are positively regulated by the TCS LisRK that responds to cell envelope stress [ 71 , 72 , 76 , 77 ]. Transcription of all LhrC sRNAs except Rli22 is strongly induced during intracellular bacterial growth in murine macrophages.…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%